2015
DOI: 10.4103/0975-7406.155816
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between arch form and facial form: A cross sectional study

Abstract: Arch form is a key determinant in teeth position. Teeth selection and placement must be based on the functional and esthetic needs of the patient. Keeping in mind, the biomechanics involved with the prosthesis. The aim of the study was to evaluate the correlation between arch form and facial form. About 40 individuals in the age group of 20-25 years were involved in the study. The arch form and facial form were analyzed statistically to check for any correlation. It was found that, 63.63% of leptoprosophic ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
2
1
0
Order By: Relevance
“…In the present study it was seen that a statistically significant correlation existed between face form and arch form (p<0.001). This was similar to the studies conducted by Nayar et al 22 and Sellen et al 23 However, no correlation was found among rugae pattern with the face form and arch form.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study it was seen that a statistically significant correlation existed between face form and arch form (p<0.001). This was similar to the studies conducted by Nayar et al 22 and Sellen et al 23 However, no correlation was found among rugae pattern with the face form and arch form.…”
Section: Discussionsupporting
confidence: 91%
“…The mean interpremolar, intermolar dental and interpremolar, intermolar alveolar arch width in both maxillary and mandibular arches were found to be highest in hypodivergent patients and least in hyperdivergent patients, which was not found to be statistically significant. This is in conformance with the researches done by Uysal et al (2005), 15 Khera et al (2012), 8 Ribeiro et al (2012), 19 Grippaudo et al (2013), 20 Bhutta et al (2013), 1 Shahroudi and Etezadi (2013), 21 Prasad et al (2013), 22 Bălan et al (2014), 23 Nayer et al (2015), 24 Traldi et al (2015), 25 Gupta and Makhija (2016), 26 Perez et al (2016), 27 Aditi et al (2017), 28 and Nagrajmurthy (2017). 29 However, the data from this study presented an antithetical fashion between SN-MP angle and dental arch widths, the relationship was less strong, which showed that the SN-MP angle might not be only one of the contributing factors.…”
Section: Discussionsupporting
confidence: 79%
“…A team of Indian researchers linked face shape and dental arch in a survey of 40 people aged 20-25. Statistical analysis revealed that 54.6 % of persons with a mean facial type had an egg-shaped dental arch while 63.6 % of persons with a narrow facial type had a square arc [19].…”
Section: Discussionmentioning
confidence: 98%